The analysis of methods for assessing the methylation of cytosine residues in the DNA sample of monocarpic plant Linum usitatissimum - Berestyanaya, A.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
The advantages and disadvantages of the most popular methods of analyzing the epigenome of plants are considered. The methods of determination of the DNA methylation in the context of radio-biological researches are analyzed. Data on applications of the methods described to the study of a DNA modification of monocarpic plant Linum usitatissimum irradiated with different doses of ionizing radiation are presented.